Application Effect of ICG Fluorescence Real-Time Imaging Technology in Laparoscopic Hepatectomy - Chen, Hao; Wang, Yumin; Xie, Zhiguo; Zhang, Luyuan; Ge, Yongsheng; Yu, Jihai; Zhang, Chuanhai; Jia, Weidong; Ma, Jinliang; Liu, Wenbin (Frontiers in Oncology, 2022)
To evaluate the efficiency and safety of indocyanine green ICG fluorescence real-time guided imaging in laparoscopic hepatectomy. A retrospective analysis of patients with primary liver cancer in First Affiliated Hospital of USTC from January 2018 to October 2021, including 48 cases of fluorescence-guided laparoscopic hepatectomy (FGLH) and 60 cases of traditional laparoscopic hepatectomy (LH). The R0 resection rate, operation time, intraoperative blood loss, complications, hospital stay and other intraoperative and postoperative indicators of the two groups were analyzed to determine the clinical feasibility and safety of ICG fluorescence real-time imaging guided technology in laparoscopic hepatectomy. Search for retrospective cohort studies and randomized controlled trials comparing FGLH with LH in related databases, screen literature according to preset inclusion and exclusion criteria, evaluate literature quality, and extract data. Revman 5.3 software was used to conduct Meta analysis on the extracted data. Both the results of our own clinical data and Meta-analysis showed that compared with LH group, FGLH increased the R0 resection rate; shortened the operation time and postoperative hospital stay; reduced blood losing and the occurrence of postoperative complications. Compared with LH, FGLH has a better application effect in laparoscopic hepatectomy, and it is worthy of promotion as its safe and feasible.